(untitled) (Research, Society and Development, 2021)
Naphazoline has been proven to be effective in reducing the manifestations of nasal obstruction, which affects people’s quality of life so much, but its benefits have been distorted, putting human health at risk, especially when there is uncontrolled and prevalent use. Some excipients used in naphazoline hydrochloride can cause a significant decrease in lung function and hypersensitivity reactions in asthmatic patients, in addition to aggravating drug-induced rhinitis caused by nasal decongestants. The ease of obtaining nafazoline contributes to the aggravation of some pre-existing pathologies and the appearance of adverse effects due to incorrect use, substance dependence, and in some cases it can cause some other pathologies such as drug-induced rhinitis, and the potentiation of effects in contact with other medications. The lack of knowledge, the risks of self-medication, sale without a prescription, the low cost and supply of these decongestants are factors that influence the disordered consumption of the medication, a serious public health problem. The current study aims to analyze the risks of self-medication, and the incorrect use of nasal decongestants that have Naphazoline Hydrochloride in their composition and the pharmacist as the protagonist for the rational use of medicines.: naphazoline hydrochloride, naphazoline, imidazoline derivatives, naphazoline intoxications, naphazoline dependence, nasal decongestants, drug-induced rhinitis. Pharmaceutical guidance is essential to guide the correct use of the drug, as this professional has specific knowledge about drugs in general, regardless of their class and what benefits and risks they can offer to health in order to avoid future pathologies, in addition to contributing with the national policy on the correct use of medicines. The pharmacist has an important role in helping society, promoting health education about the use of medication and its main adverse effects, intervening in self-medication and minimizing it.